A contribution for the improvement in thermal insulation of tabique walls coated with metal corrugated sheets. (July 2015) - Cunha, Sandra; Pinto, Jorge; Paiva, Anabela; Briga-Sá, Ana; Soares, Nuno; Varum, Humberto; Ferreira, Débora
Tabique is a traditional Portuguese building technique using timber and earth and was intensively applied until the 20th century. There is an impressive tabique heritage that requires maintenance and rehabilitation interventions. Taking into account the facts that technical and scientific publications related to this particular technique are lacking and that the technique is also applied worldwide, this research work is a very relevant one. This study aims at studying the thermal insulation behaviour of tabique walls and in particular, tabique walls coated using metal corrugated sheets and thermally reinforced with an insulation material. This type of building component is initially characterized and some building details concerning the metal corrugated sheet coating are described. An experimental work was conducted to determine the thermal transmission coefficient of the tabique wall samples. It was concluded that providing the tabique wall coated with metal corrugated sheets with a 3 cm extruded polystyrene board results in a thermal insulation improvement of 61%. These results revealed that the thermal insulation reinforcement of tabique walls is possible and it may be a straightforward building procedure because it can be achieved using the thermal insulation building materials that are currently being used. Therefore, the thermal insulation reinforcement of tabique walls seems feasible. Furthermore, the thermal insulation parameters obtained in this study are similar to the ones obtained for currently applied walls solutions in new buildings. This technical fact may provide guidance for the possibility of using solutions used in old buildings to meet the thermal comfort requirements expected in today's times. The knowledge gained will also be useful to support future proposals of energy rehabilitation solutions. Practical implications: In this article, tabique construction and its relevance worldwide are discussed. This article highlights the building details concerning the use of metal corrugated sheet coating on tabique walls and evaluates the thermal insulation behaviour of this wall system. The outcomes indicate that it is possible to improve the thermal insulation of a tabique wall. The data obtained in this study may be valuable for repairing tabique walls and may also inspire innovative building solutions in modern industrial practice.